2015
DOI: 10.1097/brs.0000000000001020
|View full text |Cite
|
Sign up to set email alerts
|

Radiographical and Implant-Related Complications in Adult Spinal Deformity Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(68 citation statements)
references
References 44 publications
1
66
1
Order By: Relevance
“…Surgery for adult spinal deformity (ASD) has increased in magnitude and complexity, and often deformities require three-column osteotomies (3COs) such as pedicle substraction osteotomy (PSO) or vertebral column resection (VCR) [1][2][3][4][5][6][7]. While operative management is known to be associated with greater quality-adjusted life years than non-operative treatment [8], complication rates of up to 50% have been reported in this patient population [1,2,7,[9][10][11][12][13][14][15]. Apart from one recent study [14], most of the data came from retrospective cohorts with poorly defined inclusion criteria and lacked validated assessment systems.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery for adult spinal deformity (ASD) has increased in magnitude and complexity, and often deformities require three-column osteotomies (3COs) such as pedicle substraction osteotomy (PSO) or vertebral column resection (VCR) [1][2][3][4][5][6][7]. While operative management is known to be associated with greater quality-adjusted life years than non-operative treatment [8], complication rates of up to 50% have been reported in this patient population [1,2,7,[9][10][11][12][13][14][15]. Apart from one recent study [14], most of the data came from retrospective cohorts with poorly defined inclusion criteria and lacked validated assessment systems.…”
Section: Introductionmentioning
confidence: 99%
“…To more fully explore in impact of obesity on the entire spine, Teraguchi et al [24] investigated the prevalence and distribution of intervertebral disc degeneration over the entire spine and found the age and obesity were associated with the presence of disc degeneration in all areas of the spine, indicating that obesity places stress across multiple regions of back. BMI and obesity have also been identified as a risk factor for adjacent segment diseases and post-operative complications among patients undergoing lumbar fusion for degenerative spine diseases [30,31,32,33,34,35,36,37,38,39,40]. Weight control before and after the surgery was observed to reduce the incidence of adjacent segment disease and improve the fusion surgery outcome [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Although several recent series have highlighted the correlation between sagittal balance and spinopelvic parameters and self-reported outcomes, both before 4850 and after surgical treatment for patients with ASD, 50,51 due to the novelty of such concepts, the incorporation of the preoperative evaluation of such parameters is still not reflected in the reported outcomes available in the literature as a whole. In objective terms, the largest prospective multicenter study involving both operative and nonoperative treatment of patients with ASD has demonstrated that a pelvic tilt (PT) of 22° or more, an sagittal vertical axis of 47 mm or more, and pelvic incidence minus lumbar lordosis (PI − LL) of 11° or more can be used as key threshold values for identifying patients with severe disability (ODI > 40).…”
Section: Conclusion and Implications For Future Researchmentioning
confidence: 99%